Exploring Sex Differences in the Association between Bullying Involvement and Alcohol and Marijuana Use among U.S. Adolescents in 6th to 10th Grade. (1st May 2020) - Lee, Jungup; Choi, Mi Jin; Thornberg, Robert; Hong, Jun Sung
Abstract: Objectives: The aim of the current study was to examine whether different types of involvement in bullying, together with a set of social-ecological correlates, were associated with alcohol and marijuana use for female and male adolescents. Methods: This study utilized data derived from the U.S. division of the 2005–2006 Health Behavior in School-Aged Children (HBSC) study, which include 7, 084 U.S. 6 th –10 th graders (3, 353 males and 3, 731 females) in public and private schools. Results: The results showed that although some forms of involvement in bullying were associated with alcohol and marijuana use, some of these associations became non-significant when the social-ecological covariates were included in the models. The final logistic regression models revealed that being a traditional bully-victim increased the risk of alcohol use for males while being a traditional bully and cyber victim increased the risk of alcohol use for females. In addition, being a cyberbully increased the risk of marijuana use for males. While parental monitoring decreased the risk, delinquent peers increased the risk of both alcohol and marijuana use for both sexes. Parent/guardian support decreased the risk of alcohol use for females. The likelihood of alcohol use and marijuana use increased with age for both sexes, while being an African American was linked with a lower risk of alcohol and marijuana use among males. Conclusions/Importance: Our findings demonstrate the importance of examining the link between bullying involvement and substance use, together with social-ecological correlates for female and male adolescents.